2004
DOI: 10.3748/wjg.v10.i21.3171
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of endothelial surface by an increase of vessel diameter during tumor angiogenesis in experimental hepatocellular and pancreatic cancer

Abstract: The expansion of endothelial cells during tumor angiogenesis is accompanied to a large extent by an increase of vessel diameter rather than by formation of new blood vessels. This may be a possible adaptive mechanism by which experimental pancreatic and hepatocellular cancers expand their endothelial diffusion surface of endothelium to compensate for inadequate neoangiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Notably, increasing vessel heterogeneity and chaotic vessel organization were only observed late in tumorigenesis, when the carcinoma had progressed beyond the nodular stage. These findings are similar to those in our earlier studies, using a mouse model of insulinoma (3) and rat hepatocellular cancer (4), where early phases of angiogenesis are marked by an increase in vessel diameter rather than vessel numbers. Thus, expansion of the endothelial surface area is the first adaptive process of the vasculature during tumorigenesis.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Notably, increasing vessel heterogeneity and chaotic vessel organization were only observed late in tumorigenesis, when the carcinoma had progressed beyond the nodular stage. These findings are similar to those in our earlier studies, using a mouse model of insulinoma (3) and rat hepatocellular cancer (4), where early phases of angiogenesis are marked by an increase in vessel diameter rather than vessel numbers. Thus, expansion of the endothelial surface area is the first adaptive process of the vasculature during tumorigenesis.…”
Section: Discussionsupporting
confidence: 81%
“…During neovascularization, endothelial cells, which form the lining of blood vessels, proliferate, invade into surrounding stroma, and finally form new vascular sprouts. Due to constant vessel remodeling, the tumor vasculature develops distinct and stage-specific morphologic features compared with their normal counterparts (3,4). Molecular events that direct angiogenesis have been extensively studied in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The reduced cellular density and the presence of RBCs account for the elevated ADCs and reduced T 2 values, respectively, in contrast to V1 (Table 2). Previous reports by Ryschich and coworkers (41, 42) showed that vessel dilation is the first detectable stage of ongoing angiogenesis and occurs prior to vessel sprouting. The authors concluded that vessel dilation permits an increased endothelial diffusion surface for delivery of O 2 to surrounding tissue.…”
Section: Discussionmentioning
confidence: 91%
“…However, this is for the average concentration throughout the entire tumor, whereas in the current calculation, the AuNPs are limited to the tumor vasculature. If blood vessels make up 5% of the tumor volume (33) and the AuNPs are restricted to them, then the average concentration in the blood vessels will be 20 times the overall concentration (i.e., 140 mg/g for a total tumor concentration of 7 mg/g). Work by Perrault et al (6) shows that a majority of passively targeted 100-nm AuNPs will remain along the tumor blood vessel walls 8 h after injection.…”
Section: Number Of Aunps Per Endothelial Cellmentioning
confidence: 99%